Do networks really work? a framework for evaluating public sector organizational network - Provan, Keith G.; Milward, H. Brinton (2001)
Although cooperative, interorganizational networks have become a common mechanism for delivery of public services, evaluating their effectiveness is extremely complex and has generally been neglected. To help resolve this problem, we discuss the evaluation of networks of community-based, mostly publicly funded health, human service, and public welfare organizations. Consistent with pressures to perform effectively from a broad range of key stakeholders, we argue that networks must be evaluated at three levels of analysis: community, network, and organization/participant levels. While the three levels are related, each has its own set of effectiveness criteria that must be considered. The article offers a general discussion of network efectiveness, followed by arguments explaining effectiveness criteria and stakeholders at each level of analysis. Finally, the article examines how effectiveness at one level of network analysis may or may not match effectiveness criteria at another level and the extent to which integration across levels may be possible. - Reproduced
Keywords: Public sector - United States; Public sector